Modifying the Process Evaluation Framework for Utilization in Extension and Social Sciences - Stacey F. Stearns; Cristina Connolly; Jeantyl Norze (Journal of International Agricultural and Extension Education, 2025)
Medical fields use process evaluations to measure intervention fidelity as they are often complex with multiple interacting components. While Cooperative Extension programs are similarly structured, process evaluations have not been widely used in Extension or other social sciences, but could be beneficial in improving programming using a modified framework. We modified Carroll et al.’s framework to conduct a process evaluation of an Extension program instead of in a medical field. This paper outlines the implementation fidelity using ex-post, semi-structured interviews conducted based on the process evaluation framework. The interviews helped complete the process evaluation and address data gaps.
Keywords: Process Evaluation; Program Evaluation; Cooperative Extension; New Technologies in Agricultural Extension; Game-based Learning; Team Development; Program Fidelity; Program Adaptation